A novel multiscale material plasticity simulation model for high-performance cutting AISI 4140 steel - Bai, Jinxuan; Tong, Zhen (International journal of advanced manufacturing technology, 2021)
The achievable machined surface quality relies significantly on the material behavior during the high-performance cutting process. In this paper, a multiscale material plasticity simulation framework is developed to predict the deformation behaviors of AISI 4140 steel under various high-performance cutting conditions. The framework was built by coupling a three-dimensional discrete dislocation dynamic (3D-DDD) model with a finite element method (FEM) through the optimization of a dislocation density-based (DDB) constitutive equation (compiled as a user-defined subroutine in ABAQUS). The movement of edge and screw dislocations such as generation, propagation, siding, and their interactions, was performed by 3D-DDD, and the statistical features of dislocations were used to optimize the critical constants of the DDB constitutive equation. For validation, a classic FEM cutting model (Johnson-Cook constitutive equation) was employed as a reference. The simulation results indicated that the proposed multiscale model not only can precisely predict the stress, strain, cutting force, and temperature as those predicted by the classic FEM simulations, but also capture the microstructure characteristics such as grain size and dislocation density distributions under the tested cutting conditions. Severe dynamic recrystallization phenomena were found at the core shear zones. The recrystallization process reached a dynamic equilibrium at the machined surfaces when the cutting speed is larger than 280 m/min or the external-assisted temperature is between 200 and 350°, indicating an optimal range of machining parameters for improved surface integrity.